Australian Clinical Legal Education: Designing and operating a best practice clinical program in an Australian law school - Evans, Adrian (ANU Press, 2017)
Clinical legal education (CLE) is potentially the major disruptor of traditional law schools' core functions. Good CLE challenges many central clichés of conventional learning in law-everything from case book method to the 50-minute lecture. And it can challenge a contemporary overemphasis on screen-based learning, particularly when those screens only provide information and require no interaction. Australian Clinical Legal Education comes out of a thorough research program and offers the essential guidebook for anyone seeking to design and redesign accountable legal education; that is, education that does not just transform the learner, but also inculcates in future lawyers a compassion for and service of those whom the law ought to serve. Established law teachers will come to grips with the power of clinical method. Law students struggling with overly dry conceptual content will experience the connections between skills, the law and real life. Regulators will look again at law curricula and ask law deans 'when'?